Prendre la plume pour s’imposer dans le parti ? Le cas de Therese Schlesinger, militante du Parti social-démocrate autrichien - Jean-Numa Ducange (Genre & Histoire)
The article presents Therese Schlesinger, a major figure of Austrian social democracy, in particular her articles published in the leading journals of the German Social Democracy. It shows how a lots of its publications, including many reviews of books, helped make a major feminist figures of the time, at the crossroads of two contries, Austria and Germany. One of his contributions on the history of women is published at the time of "revisionist" crisis, which puts into question the foundations of marxism. This publication shows the ability to Schlesinger, capable of mobilizing different currents service its main cause: the battle for recognition of the legitimacy of feminist struggles in the labor movement.